ANALYSIS OF FACTORS INFLUENCING REPURCHASE INTENTION IN AUTOMOTIVE COMPANIES IN BATAM CITY - Ratih Anggraini; Roby Tan; Siti Rohani (Journal of Global Business and Management Review, 2025)
This study aims to analyze the influence of innovation, digitalization, and product innovation on repurchase intention, using automotive companies in Batam City as the research object. The research applies a quantitative approach, where primary data were collected through the distribution of questionnaires to 400 respondents who are car users from various automotive companies in Batam City. The questionnaire consisted of 16 items, measured using a 5-point Likert scale, and distributed via Google Forms. The data collection was conducted between December 2023 and February 2024. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SMART-PLS software. The results show that innovation, digitalization, and product innovation each have a significant positive effect on repurchase intention. These findings suggest that the implementation of innovation and digital transformation, along with continuous product development, play a crucial role in increasing customer loyalty and repurchase intention in the automotive industry.